2004
DOI: 10.1158/1078-0432.ccr-04-0764
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Nuclear Localization Is Predictive of Biochemical Recurrence in Patients with Positive Margin Prostate Cancer

Abstract: Purpose: Radical prostatectomy (RP) patients with positive surgical margins are at increased risk for recurrence, emphasizing the need for prognostic markers to stratify probable outcome for optimal patient management decisions. We tested the hypothesis that nuclear localization of nuclear factor (NF)-B, a transcription factor involved in the regulation of cell growth, angiogenesis, invasion, and apoptosis, is associated with an increased risk of biochemical recurrence after RP.Experimental Design: Analyses ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
95
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 31 publications
9
95
1
2
Order By: Relevance
“…However, NF-kB nuclear localisation was unrelated to the risk of biochemical relapse (Ross et al, 2004). Notably, the rate of nuclear NF-kB staining (15%) in the study by Ross et al was lower than what we report in the present study (54.7%) or other reports (Fradet et al, 2004). We showed that the antibody used in the present work detected nuclear translocation (activation) of NF-kB/p65 under controlled experimental cell culture conditions.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…However, NF-kB nuclear localisation was unrelated to the risk of biochemical relapse (Ross et al, 2004). Notably, the rate of nuclear NF-kB staining (15%) in the study by Ross et al was lower than what we report in the present study (54.7%) or other reports (Fradet et al, 2004). We showed that the antibody used in the present work detected nuclear translocation (activation) of NF-kB/p65 under controlled experimental cell culture conditions.…”
Section: Discussioncontrasting
confidence: 70%
“…Of note in this study was the fact that nuclear NF-kB expression was not specifically linked with disease relapse. However, in another study performed in patients with prostate cancer and pathologically positive surgical margins in the prostatectomy specimens, NF-kB nuclear localisation was associated to a high risk of biochemical relapse (Fradet et al, 2004).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The prognostic value of RelA is in concordance with studies on prostate cancer, in which both nuclear and cytoplasmic RelA overexpression were linked to disease progression (Fradet et al, 2004;Ross et al, 2004). In gastric adenocarcinoma, the prognostic impact of RelA expression appears to be somewhat conflictive, as overexpression was reported both to be an indicator of adverse (Sasaki et al, 2001;Yamanaka et al, 2004) and favourable (Lee et al, 2005) patient prognosis.…”
Section: Shuklasupporting
confidence: 70%
“…Here, we found the NF-kB subunit RelA to be overexpressed in roughly half of a large set of pancreatic adenocarcinomas analysed. Overexpression of cytoplasmic and/or nuclear RelA in tumour tissue has been previously observed in larger study cohorts of gastric (Sasaki et al, 2001;Yamanaka et al, 2004;Cao et al, 2005;Lee et al, 2005), prostate (Fradet et al, 2004;Ismail et al, 2004;Ross et al, 2004; Figure 2 Kaplan -Meier survival curves in dependence of clinicopathological factors and RelA/p65 expression patterns. Overall survival dependent on nodal status (A) and grade (B).…”
Section: Discussionmentioning
confidence: 59%